2014
DOI: 10.1021/sc500044p
|View full text |Cite
|
Sign up to set email alerts
|

Surface Modification of Membrane Filters Using Graphene and Graphene Oxide-Based Nanomaterials for Bacterial Inactivation and Removal

Abstract: Surfaces of commercially available membrane filters were modified by the dispersion of poly(N-vinylcarbazole) (PVK), graphene (G), poly(N-vinylcarbazole)-graphene (PVK-G), graphene oxide (GO), and poly(Nvinylcarbazole)-graphene oxide (PVK-GO) in order to impart antibacterial properties. The successful coatings of the membranes were demonstrated through scanning electron microscopy (SEM) and Fourier transform infrared (FT-IR) spectroscopy. Investigations carried out on the surface-modified membrane filters usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
146
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 212 publications
(149 citation statements)
references
References 28 publications
2
146
0
1
Order By: Relevance
“…2(C) is the schematic for possible water vapor transport method through GO membrane. Nair et al [1] explains that the GO laminates are made of crystallites stacked on top of each other and the hydroxyl and epoxy groups attached to the graphene sheets offers spacing between the Water transport [50] Ozonated graphene oxide membrane Proton exchange [54] Graphene oxide membrane filters Bacterial inactivation and removal [56] Graphene oxide membrane Desalination [60] membranes. According to their model and explanation, the pristine graphene capillaries are wide open to accommodate the water molecule and the capillaries becomes narrow in low humidity, which do not provide enough Vander-Waals distance to accommodate water molecules and this mechanism is shown in the Fig.…”
Section: Go Membranes For Gas Separationmentioning
confidence: 99%
See 1 more Smart Citation
“…2(C) is the schematic for possible water vapor transport method through GO membrane. Nair et al [1] explains that the GO laminates are made of crystallites stacked on top of each other and the hydroxyl and epoxy groups attached to the graphene sheets offers spacing between the Water transport [50] Ozonated graphene oxide membrane Proton exchange [54] Graphene oxide membrane filters Bacterial inactivation and removal [56] Graphene oxide membrane Desalination [60] membranes. According to their model and explanation, the pristine graphene capillaries are wide open to accommodate the water molecule and the capillaries becomes narrow in low humidity, which do not provide enough Vander-Waals distance to accommodate water molecules and this mechanism is shown in the Fig.…”
Section: Go Membranes For Gas Separationmentioning
confidence: 99%
“…Such type of scalable GO membranes has futuristic applications in regenerative medicine. In another work, Rodrigues et al [56] has reported the usefulness of graphene oxide modified membranes for the removal of bacteria and their inactivation. The reported superior antibacterial activity of these modified membranes was due to the production of reactive oxygen species (ROS) which is capable of damaging the bacterial cell and hinders their metabolic activity which in turn inhibit the bacterial growth.…”
Section: Go Membrane As Ionic and Molecular Sieve In Solutionmentioning
confidence: 99%
“…Contamination of surface waters also constitutes a risk to water supplies because pollutants may penetrate into aquifers, where they can be transported to drinking water sources. These challenges, among others, bring into focus the need for alternative water treatment and pollutant remediation methods to complement [7] or replace existing technologies.…”
Section: Introductionmentioning
confidence: 99%
“…The use of engineered nanomaterials (ENMs) for water treatment is currently limited to exploring their potential to act as effective adsorbents [8], filters [9], disinfectants [7,10,11], and reactive agents [12,13], although they show promise for full scale water treatment and environmental remediation [14][15][16]. However, relatively little progress has been made compared to the application of nanotechnology in fields such as medicine and electronics.…”
Section: Introductionmentioning
confidence: 99%
“…Portanto, o aumento de alternativas para o tratamento de água e remediação de poluentes se torna desafio para a complementação ou substituição das tecnologias existentes (QU et al, 2012;MUSICO et al, 2014).…”
Section: Introductionunclassified